2017
DOI: 10.1055/s-0037-1601329
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Antibodies against Domain I of Beta-2 Glycoprotein I in Antiphospholipid Syndrome

Abstract: The antiphospholipid syndrome (APS) is characterized by vascular thrombosis and/or pregnancy morbidity with the persistent presence of antiphospholipid antibodies (aPLs). Progress is being made in understanding the pathogenesis of the syndrome, but difficulties persist in the identification of patients at risk for thrombosis and/or pregnancy morbidity. Beta-2 glycoprotein I (βGPI), a plasma protein consisting of five sushi domains, is thought to be the main antigenic target of aPLs. Antibodies recognizing doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 81 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…The effect of aCL and anti- β 2 GPI is evident in myocardial ischemia, myocarditis and valvular disease, which is related to the types and titers of antibodies ( Djokovic et al, 2022 ). According to existing literature, the mechanism is not only associated with thrombosis but also includes inflammation, complement pathways, platelet activation, etc ( Kelchtermans, Chayouâ & Laat, 2018 ; Pengo et al, 2010 ; Stojanovich et al, 2013 ). As previously mentioned, the deposition of anti- β 2GPI and complement in heart valves can cause inflammation, immune responses ( Zuily et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of aCL and anti- β 2 GPI is evident in myocardial ischemia, myocarditis and valvular disease, which is related to the types and titers of antibodies ( Djokovic et al, 2022 ). According to existing literature, the mechanism is not only associated with thrombosis but also includes inflammation, complement pathways, platelet activation, etc ( Kelchtermans, Chayouâ & Laat, 2018 ; Pengo et al, 2010 ; Stojanovich et al, 2013 ). As previously mentioned, the deposition of anti- β 2GPI and complement in heart valves can cause inflammation, immune responses ( Zuily et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against all five domains of β2GPI may develop, but in APS the pathogenic groups of anti-β2GPI are thought to primarily recognize the first domain (domain I, DI), which becomes exposed upon closed-to-open conformational change. [54][55][56] In contrast, domain V (DV) is exposed in both conformations and contains regions that interact with cell surface molecules such as phospholipid and receptors. 51,55,56 Antibodies to domain V are considered nonpathogenic 57 and may be more common in people with transient aPL positivity following infection and clearance, 58,59 whereas anti-DI antibodies cause thrombosis 60,61 and pregnancy loss in mouse models of APS.…”
Section: Defining Antiphospholipid Syndromementioning
confidence: 99%
“…[54][55][56] In contrast, domain V (DV) is exposed in both conformations and contains regions that interact with cell surface molecules such as phospholipid and receptors. 51,55,56 Antibodies to domain V are considered nonpathogenic 57 and may be more common in people with transient aPL positivity following infection and clearance, 58,59 whereas anti-DI antibodies cause thrombosis 60,61 and pregnancy loss in mouse models of APS. 60 Studies of anti-DI in patient sera show definitive associations with the syndrome 62 and predominantly vascular complications in primary and SLE-associated APS.…”
Section: Defining Antiphospholipid Syndromementioning
confidence: 99%
“…It is primarily synthesized by liver cells and comprises five domains (I–V) [ 5 ]. APOH is a complement regulator across diverse biological processes and conditions, including antiphospholipid syndrome (APS), the procoagulant state, diabetes, and immune disorders [ 6 8 ]. Furthermore, studies have indicated APOH’s involvement in innate immunity by binding to viruses and bacteria [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is primarily synthesized by liver cells and comprises five domains (I-V) [5]. APOH is a complement regulator across diverse biological processes and conditions, including antiphospholipid syndrome (APS), the procoagulant state, diabetes, and immune disorders [6][7][8].…”
Section: Introductionmentioning
confidence: 99%